2015
DOI: 10.1103/physrevb.92.115112
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism and metal-insulator transition in oxygen-deficientSrTiO3

Abstract: First-principles calculations to study the electronic and magnetic properties of bulk, oxygendeficient SrTiO3 (STO) under different doping conditions and densities have been conducted. The appearance of magnetism in oxygen-deficient STO is not determined solely by the presence of a single oxygen vacancy but by the density of free carriers and the relative proximity of the vacant sites. We find that while an isolated vacancy behaves as a non-magnetic double donor, manipulation of the doping conditions allows th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 36 publications
5
45
0
Order By: Relevance
“…Additional removal of a charge carrier from the CB leads to a semiconducting system with the magnetic moments intact. This result is similar to the single-hole doped mono-Ov 8 and suggests that up to n-hole doping (n ≡ Ov concentration), the defect levels are pinned at ∼0.5 eV below the bottom of the conduction band. Further removal of a third electron localizes the remaining electron in a vacant site, yielding a total magnetic moment of 1 µ B .…”
Section: +supporting
confidence: 75%
See 2 more Smart Citations
“…Additional removal of a charge carrier from the CB leads to a semiconducting system with the magnetic moments intact. This result is similar to the single-hole doped mono-Ov 8 and suggests that up to n-hole doping (n ≡ Ov concentration), the defect levels are pinned at ∼0.5 eV below the bottom of the conduction band. Further removal of a third electron localizes the remaining electron in a vacant site, yielding a total magnetic moment of 1 µ B .…”
Section: +supporting
confidence: 75%
“…We use correlated band theory to predict magnetic behaviour in mOv and develop a comprehensive F-center analysis that accounts for the varied defect possibilities in SrTiO 3−δ . Unlike O monovacancies which may exhibit localized magnetic moments for particular doping concentrations or vacancy densities, 8 for any doping density, we find that isolated mOv always exhibit intrinsic magnetic moments. Both neutral and charged mOv configurations are considered to account for the effect of doping in spin alignment.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…Calculations based on density functional theory (DFT) using hybrid functionals or employing static correlation effects from a Hartree-Fock-like treated Hubbard Hamiltonian ('+U') can reveal some relevant aspects of the intriguing electronic structure [15][16][17][30][31][32][33][34]. But there are two serious drawbacks to such extended KohnSham schemes.…”
Section: Introductionmentioning
confidence: 99%
“…Though a deeper relevance of these defects for the formation of the original quasi-twodimensional electron liquid is still under debate, several first-principles calculations have shown that even the stoichiometric heterostructure is metallic from partly filled Ti(t 2g )-dominated bands at the Fermi level. Although there are other theoretical suggestions [32,[36][37][38][39][40], OVs provide a natural way to explain the occurrence of interface ferromagnetism [16,19,30,34]. In conventional DFT, an OV induces crystal-field lowered e g -like impurity states on the neighboring Ti ions.…”
Section: Introductionmentioning
confidence: 99%